Peasants‘ knowledge, peasants‘ self-organisation and peasants‘ resistance in Belarus - Berghuber, Konrad (Momentum Quarterly, 2015)
The present article observes peasants‘ self organisation, local knowledge and resistance against the dominant classes at the territory of Belarus since abolishing serfdom in 1861. It relates them to the discussion about commons and to anarchist ideas about peasants‘ life as an example for a solidarity society. The Obschtschina and co-operations in the production and use of machinery during the soviet “new economic policy” provide references for peasants‘ self-organization. Local knowledge is situated in the Obschtschina and in the small scale private farms of the workers of the sovkhozes and kolkhozes. Due to their situation peasants acted in a way of open resistance against the dominant classes until the 1930ies. This resistance reached its peaks during the revolutions of 1905-07 and of 1917, during the time of collectivizing peasants‘ farms and during the economic crisis at the beginning of the 1930ies. After the implementation of the kolkhozes and sovkhozes peasants‘ resistance got a more hidden form. These peasants‘ struggles for land and independence are comparable to peasants‘ struggles in other countries.